Implementation of Corporate Social and Environmental Responsibility of Mining Companies in Palu City - Andi Muh. Fadly; Suarlan Datupalinge; Ratu Ratna Korompot (Rechtsvinding, 2026)
The purpose of this study is to discuss the implementation of Social and Environmental Responsibility (TJSL) with a case study at PT. Citra Palu Mineral. This study uses an empirical juridical method. The results show that TJSL in Indonesia has developed from a voluntary concept to a legal obligation regulated in various regulations. PT. CPM has basically prepared a TJSL master plan that refers to the provincial and city RPJMD, but implementation in the field is still perceived by the community as limited and not commensurate with the company's profits. The company claims to have implemented broader programs, both in the social and environmental fields according to the principles of good mining practice, including land reclamation and changes in mining methods. The main obstacles faced by the company include the diversity of urban community needs that are difficult to map and the public perception that still equates TJSL with cash assistance. This study concludes that there is a gap between regulations, company practices, and community expectations. Therefore, it is recommended that PT. CPM improves coordination with local governments and local stakeholders, expands the scope of community empowerment programs, and conducts outreach regarding the TJSL concept to create a harmonious understanding between the company and the community.